2014
DOI: 10.4049/jimmunol.1400959
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant TLR/RLH Signaling of Radioresistant and Radiosensitive Cells Is Essential for Protection against Vesicular Stomatitis Virus Infection

Abstract: Several studies indicated that TLR as well as retinoic acid–inducible gene I–like helicase (RLH) signaling contribute to vesicular stomatitis virus (VSV)–mediated triggering of type I IFN (IFN-I) responses. Nevertheless, TLR-deficient MyD88−/−Trif−/− mice and RLH-deficient caspase activation and recruitment domain adaptor inducing IFN-β (Cardif)−/− mice showed only marginally enhanced susceptibility to lethal VSV i.v. infection. Therefore, we addressed whether concomitant TLR and RLH signaling, or some other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

7
2

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…In contrast, only mice lacking both signaling pathways were unable to produce IFN-␤ in response to challenge with TMEV. A similar observation was made in a recent study with VSV in which both TLRs and RLRs were found to be necessary to mount a protective IFN response (27).…”
Section: Discussionsupporting
confidence: 57%
“…In contrast, only mice lacking both signaling pathways were unable to produce IFN-␤ in response to challenge with TMEV. A similar observation was made in a recent study with VSV in which both TLRs and RLRs were found to be necessary to mount a protective IFN response (27).…”
Section: Discussionsupporting
confidence: 57%
“…TLRs have been implicated in protection against VSV in both in vivo knockout studies (10) and cell culture of dendritic cells (11) and macrophages (12). The TLRs found to be upregulated (TLR1, TLR6, and TLR10) at D0 have not been reported in the context of VSV, but our data suggest that TLR signaling participates in the immunogenicity of VSV⌬G/EBOVgp, as it has in other vaccines (13).…”
mentioning
confidence: 39%
“…Different lines of transgenic mice, all on the C57BL/6 genetic background, were used in the study: WT C57BL/6J mice (Charles River) and several knockout (KO) models: mice deleted for IFN-I receptor (IFNAR-KO) [8], RLR adaptor protein MAVS (MAVS-KO) [9], TLR adaptor protein MyD88 (MyD88-KO) [10], and TLR-3 receptor (TLR3-KO) [11], and mice crossed to bear several deletions, including MyD88/ TRIF-KO, MyD88/MAVS-KO and MyD88/TRIF/MAVS-KO [12].…”
Section: Infection Of Micementioning
confidence: 99%